The effect of gossypol acetate on the fertility of boars - Torres, Mariana; Balogun, Kayode; Shirley, Larissa; de Andrade, André Furugen Cesar; Stewart, Kara; Hu, Keping; Wang, Xiaoying; Machaty, Zoltan (Acta Agraria Debreceniensis, 2022)
This study evaluated the effect of gossypol acetate, a potential antifertility compound, on semen quality and testicular histopathology of boars. Six boars were allotted into two experimental groups. Half of the animals were fed a diet that was supplemented with 2 mg of gossypol acetate per kg body weight per day for 9 weeks, control animals received a gossypol acetate-free feed. During the experimental period, semen was collected weekly from each boar and semen parameters were recorded. The animals were then euthanized, testicular samples were collected and histopathological examination of the testicular cells, as well as morphometrical analysis of the seminiferous tubules, were performed. The percentage of spermatozoa showing tail abnormalities increased significantly (P=0.017) in the semen of boars fed gossypol acetate-supplemented feed, while several other semen parameters deteriorated without showing statistical significance. Gossypol acetate supplementation also led to a decrease (P=0.042) in the number of spermatogonia in the seminiferous tubules and an increase (P=0.020) in the number of vacuoles in the seminiferous epithelium, consistent with changes seen in cases of male reproductive toxicity. In conclusion, gossypol acetate negatively affected a number of semen characteristics and also had detrimental effects on the histopathology of the testes.